Family storytelling about hereditary cancer: Framing shared understandings of risk. Issue 6 (22nd January 2020) - Campbell‐Salome, Gemme; Rauscher, Emily A.
Abstract: Family communication about the family's health history (FHH) is an important step in alerting individuals to their hereditary disease risks and facilitating prevention. Individuals often communicate about the FHH of hereditary cancer as a story, which highlights the importance of analyzing family narratives of hereditary cancer to better understand their relation to psychological and physical well‐being. This study investigates the content of family stories by examining how narrative tone and framing relate to coping, perceptions of risk, and medical decision‐making. The current study recruited 42 family dyads with a prevalent FHH of hereditary cancer to participate in dyadic phone interviews to jointly tell their family narrative of hereditary cancer. Using an iterative analysis, findings examine how families create a shared understanding of FHH and hereditary risk. Narrative tone reflects participants' psychological well‐being and contributed to the way families framed their experiences. Common frames to family narratives of hereditary cancer included empowerment, adversity, laissez faire, and discrepant. Each frame gave insight into how families were coping, their perceptions of risk, and how they make medical decisions to manage those risks. Developing a better understanding of how families communicate about their hereditary cancer risks can aid in designing clinical interventions to help families re‐frame their stories to promote improved health outcomes.